2015
DOI: 10.1071/cp14190
|View full text |Cite
|
Sign up to set email alerts
|

Growth and yield responses in wheat and barley to potassium supply under drought or moderately saline conditions in the south-west of Western Australia

Abstract: This study assessed whether more potassium (K) was required for optimal growth and grain yield of cereal crops under drought and salinity than under non-stressed conditions. In 2011, three experiments on wheat (Triticum aestivumL.) with four K rates (0, 20, 40, 80 kg K/ha), four application times (0, 5, 10, 15 weeks after sowing, WAS) and two sources (KCl, K2SO4) were conducted in the central and southern grainbelts of Western Australia. The lack of plant response to K supply at the sites of Bolgart (36 mg K/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…Consequently, low K supply on dry soils may make crops less drought-resistant, which further impairs root growth and K uptake. Our field experiments with wheat grown on low K soils (25-40 mg Colwell K/kg at 0-30 cm) in the central and southern grain belts of WA showed that K treatments (20-80 kg K/ha) enhanced K uptake, dry matter and grain yield (by 0.3-0.6 t/ha) at the drought-affected sites but not at the nonstressed sites (Ma et al 2015;Bell and Ma 2017). The findings suggest that drought stress may increase plant K requirement, and higher than normal fertiliser K supply on low K soils is likely to improve crop adaptation to low rainfall environments.…”
Section: Drought Responsementioning
confidence: 73%
See 2 more Smart Citations
“…Consequently, low K supply on dry soils may make crops less drought-resistant, which further impairs root growth and K uptake. Our field experiments with wheat grown on low K soils (25-40 mg Colwell K/kg at 0-30 cm) in the central and southern grain belts of WA showed that K treatments (20-80 kg K/ha) enhanced K uptake, dry matter and grain yield (by 0.3-0.6 t/ha) at the drought-affected sites but not at the nonstressed sites (Ma et al 2015;Bell and Ma 2017). The findings suggest that drought stress may increase plant K requirement, and higher than normal fertiliser K supply on low K soils is likely to improve crop adaptation to low rainfall environments.…”
Section: Drought Responsementioning
confidence: 73%
“…Low K decreased the number of spike-bearing tillers per plant in wheat Ma et al 2013) and barley (Andersen et al 1992;Mäkelä et al 2012). In the field, K applied at sowing or up to 5 weeks after sowing was more effective for grain yield in wheat than later application (Ma et al 2015), likely attributed to the beneficial effect of early K supply on tillering. Adequate supply of K to barley also improved straw strength and reduced head loss (C. Li, pers.…”
Section: Roots Tiller Grain Weightmentioning
confidence: 99%
See 1 more Smart Citation
“…, Table ) in the shoots and to sugar translocation into the grain through phloem loading and increased photosynthesis (Ma et al . ). Supplemental K + also enhanced grain yield of rice (Bohra & Doerffling ).…”
Section: Discussionmentioning
confidence: 97%
“…The positive effects of the optimal fertilization treatments on the wheat grain yield depended on scientific NPK fertilizer rates for wheat production and on the optimal fertilizer treatments (F312, F321) and more reasonable nutrients distribution of the optimal application treatments (A11, A12) than the conventional treatment (FDU or ADU) (Ma, Bell, Scanlan, Sarre, & Brennan, 2015;Zhan et al, 2016). Additionally, the higher NUE and PUE of the optimal fertilization treatments were due to the higher wheat grain yield and the lesser fertilizer rates than the conventional treatment and the coupling of irrigation with the fertilization (Wang, Chi, Ning, Tian, & Li, 2013).…”
Section: Effects Of Optimizing Fertilization Treatments On Degraded Saline Soilmentioning
confidence: 99%